Analysis of wastes height reduction, macrobiology and microbiology colony (fecal coli) on dry leaves composting process (Applied Research in Science and Technology, 2021)
The scattered leaf wastes can be turned into high nutrition organic fertilizer by utilizing vermicomposting methods.  The wastes will be consumed by earthworms reducing the mass of the waste and the excrement can be used as vermicompost. One of the important things regarding the potential of earthworms in vermicomposting is the consumption rate or the decrease in the waste pile heights. Also, the number of microorganism colonies can be determined using the MPN (Most Probable Number) method based on the parameters of fecal coli bacteria in SNI 19-7030-2004.  The vermicompost produced in this study comes from banyan leaves (Ficus benjamina) and bamboo leaves (Bambusa bambos). It takes 56 days for the vermicompost to ripen.  The decrease in pile heights was measured every three days using a ruler and resulted in an average reduction of 2.18 cm/day for Ficus benjamina leaves and 1.0 cm/day for Bambusa bamboos leaves. Samples of microorganisms were taken on the 28th and 56th day and the MPN value was calculated. The MPN value obtained on the 28th day was 290 MPN/g and on the 56th day was 460 MPN/g, indicating that the colony had reached the predetermined quality standard.